Childhood-onset versus adult-onset Takayasu arteritis: A study of 141 patients from Turkey - ALİBAZ ÖNER, FATMA; DİRESKENELİ, RAFİ HANER (W B SAUNDERS CO-ELSEVIER INC, 2021)
Aim: To compare childhood-onset (c-TAK) versus adult-onset Takayasu arteritis (a-TAK) patients for vascular involvement, disease activity, damage, and treatment. Methods: Patient charts from two tertiary-care centers of a pediatric and adult rheumatology clinic were reviewed. Adult patients diagnosed before the age of 18 years were included in the childhood-onset group. The activity was assessed with the physician's global assessment (PGA) and Indian Takayasu Clinical Activity Score (ITAS). The damage was evaluated with Takayasu Arteritis Damage Score (TADS) and Vasculitis Damage Index (VDI). Results: Twenty-four c-TAK (follow-up duration: 53 months) and 117 a-TAK patients (follow-up duration: 68 months) were analyzed. Aorta involvement was more prevalent (79% vs. 33%), and the median PGA score was higher in the c-TAK group (9 vs. 7), whereas the mean Indian Takayasu Arteritis Score was similar (14 vs. 13) among both groups. Median VDI score was lower for c-TAK patients (4 vs. 5), whereas TADS was similar for children and adults (8 vs. 8). Higher incidence of glucocorticoid related side-effects, a longer time to diagnosis and upper extremity claudication seemed to account for higher VDI scores in adults. Conclusion: Aorta involvement was more common among children with TAK, whereas upper extremities were relatively spared. Biologic agents were used more commonly among children which may be explained by higher rates of aortic involvement. However, c-TAK patients did not have greater cumulative damage. (C) 2020 Elsevier Inc. All rights reserved.
Keywords: Takayasu arteritis; Large-vessel vasculitis; Pediatric vasculitis; Damage